Some observations on hybridisation between closely related species of Rhopalocera (Lepidoptera: Lycaenidae, Nymphalidae) - J. A. Paterna; P. J. C. Russell; W. J. Tennent (SHILAP, 2022)
Details are provided of hybridisation between Polyommatus icarus (Rottemburg, 1775) from East Sussex (UK) and P. celina (Austaut, 1879) from Lanzarote (Canary Islands, Spain) under laboratory conditions. Comments are also made on natural hybrids between Melitaea phoebe and M. ornata occurring in Slovenia.